Effect of Gypsum on Hydration and Hardening Properties of Alite Modified Calcium Sulfoaluminate Cement - Pei Li (Materials, 2019)
Calcium sulphoaluminate cement (CSA) has the characteristics of quick hardening, high early strength and high impermeability, however its strength growth persistence in the middle and late stages (after the age of 3 days) is poor. In order to improve this disadvantage, the pilot production of alite (C3S) modified CSA (AMCSA) clinker was carried out by liquid phase manipulation and barium ion doping technology. The effects of different dosages of gypsum on the hydration and hardening properties of AMCSA, such as setting time, hydration rate, compressive strength and hydration products, were studied. The results show that the mineral content of ye’elimite, C2S, C3S and iron phase in the calcined AMCSA clinker are 48.5 wt.%, 32.6 wt.%, 11.7 wt.% and 7.2 wt.% respectively, which are close to the designed mineral composition. The stable coexistence of ye’elimite and C3S in the same clinker system is realized. The initial and final setting time of AMCSA are retarded with the increasing gypsum dosage. When the gypsum dosage is 15 wt.% under the experimental conditions in this study, the AMCSA mortar reaches the highest compressive strength at every age. The strength of AMCSA mortar at 28 days is still significantly improved compared with that at 3 days, which indicates that the shortcoming of the low strength growth persistence of CSA in the middle and late stages is improved.